ESTABLISHMENT OF A SOVEREIGN WEALTH FUND THROUGH INVESTMENT MANAGEMENT INSTITUTION IN REALISING OPTIMISATION OF FOREIGN INVESTMENT - Muhammad Trianda Kusuma; Tariq Hidayat Pangestu; Ricky Raytona (Faculty of Law, Universitas Lampung, 2021)
Investment can encourage the acceleration of a country's development. Foreign investment improve country's economy either with partial or complete control by the asset owner or depending on international agreements used in determining the scope of investment. However, several factors hinder the entry of foreign investment in Indonesia. To overcome this, government with parliament through Law Number 11 of 2020 concerning Job Creation emphasise the legal politics of forming a quo law-oriented towards improving the investment climate in Indonesia, one of which is the establishment of the Indonesian Sovereign Wealth Fund (SWF) under the name Investment Management Institution or Lembaga Pengelola Investasi (LPI). The purpose of this study is to see how the government's political will in attracting foreign investment is through the establishment of Law Number 11 of 2020 concerning Job Creation and the legitimacy of using the SWF model in the Investment Management Institute (LPI). This research uses a combination of juridical-normative and comparative case study methods. The juridical-normative method is carried out by identifying library materials. Through the comparative case study method, the research will analyse the formation and concept of SWF in India and Russia. This study found that, the LPI plays a vital role in infrastructure financing on national strategic projects and can encourage increasing national foreign exchange. Also, the exact source of institutional funds originates from foreign investors as in the Indian and Russian state mechanisms.